2019
DOI: 10.1136/bcr-2018-226805
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous pneumomediastinum and subcutaneous emphysema in a child with unknown aetiology

Abstract: Spontaneous subcutaneous emphysema and pneumomediastinum in children without any predisposing factors is a rare entity. We present a case of an adolescent boy with spontaneous pneumomediastinum. He is a 14-year-old boy brought to the hospital with an odd feeling in the neck and chest. Initial chest X-ray revealed subcutaneous emphysema and pneumomediastinum. He was further evaluated with CT thorax and abdomen with contrast which revealed extensive pneumomediastinum with associated surgical emphysema in the che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
6
0
3
Order By: Relevance
“…Another study from Taiwan found ISPM to be 50% of SPM cases [8]. Chidambaram and Donekal described SPM and subcutaneous emphysema without any predisposing factors or trauma in a 14-year-old male, who recovered with conservative treatment [9]. They did not classify or report this case as ISPM.…”
Section: Discussionmentioning
confidence: 93%
“…Another study from Taiwan found ISPM to be 50% of SPM cases [8]. Chidambaram and Donekal described SPM and subcutaneous emphysema without any predisposing factors or trauma in a 14-year-old male, who recovered with conservative treatment [9]. They did not classify or report this case as ISPM.…”
Section: Discussionmentioning
confidence: 93%
“…En diversos reportes, el tratamiento del neumomediastino incluye oxigenoterapia, vigilancia del patrón respiratorio y analgésicos 16,17 . En los pacientes asmáticos se recomienda el uso de broncodilatadores de acción corta y esteroides inhalados 18 .…”
Section: Discussionunclassified
“…El neumomediastino en niños es poco frecuente y generalmente está asociado con condiciones predisponentes, tales como asma, maniobras de Valsalva aisladas, infección por influenza o infecciones bacterianas intratorácicas (19).…”
Section: Discussionunclassified